On possibility of regulating the hardness of coatings based on titanium nitride, in the process of depositing them to metallic substrates; 3rd International Congress on Radiation Physics and Chemistry of Condensed Matter, High Current Electronics and Modification of Materials with Particle Beams and Plasma Flows - Sivkov A. A. Aleksandr Anatolyevich; Saigash A. S. Anastasiya Sergeevna; Gerasimov D. Yu. Dmitry Yurievich; Evdokimov A. A. Andrey Anatolievich (2012, 2012)
Title screen.